AVIATION INSURANCE AND RISK MANAGEMENT - Fortin, Philippe; Haeck, Louis (Assurances)

(untitled) (HEC Montréal, 2002)
This article is a collaborative effort from an academic perspective and a pragmatic approach on the risks related to the aviation industry in 2001. In the first part, we summarize the status of the aviation insurance law with its legal formation. lt is a good introduction to the second part where we discuss the new realities in the aviation insurance market since the tragedy in the United States. We do encourage the reader to consult the IATA web site at www.iata.org to see more documentation on these terrorist attacks and how IATA contributes to raising the strength of aviation security worldwide.